2016
DOI: 10.1051/swsc/2016037
|View full text |Cite
|
Sign up to set email alerts
|

Combining STEREO SECCHI COR2 and HI1 images for automatic CME front edge tracking

Abstract: COR2 coronagraph images are the most commonly used data for coronal mass ejection (CME) analysis among the various types of data provided by the STEREO (Solar Terrestrial Relations Observatory) SECCHI (Sun-Earth Connection Coronal and Heliospheric Investigation) suite of instruments. The field of view (FOV) in COR2 images covers 2-15 solar radii (Rs) that allow for tracking the front edge of a CME in its initial stage to forecast the lead-time of a CME and its chances of reaching the Earth. However, estimating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Further difficulties of CME detection in HI are caused by the jitter experienced by STEREO-B, which is the result of vibrations caused by the attitude-control reaction wheels. Kirnosov, Chang, and Pulkkinen (2016), however, combine COR-2 and HI-1 observations to automatically detect CME leading edges in the imagery, and CACTusCAT, which automatically detects CMEs in HI, was produced as part of HELCATS (Pant et al, 2016). The merits and difficulties of the manual versus automaticdetection methods are tackled directly by Yashiro, Michalek, and Gopalswamy (2008), who compare the CDAW and CACTus data sets.…”
Section: Introductionmentioning
confidence: 99%
“…Further difficulties of CME detection in HI are caused by the jitter experienced by STEREO-B, which is the result of vibrations caused by the attitude-control reaction wheels. Kirnosov, Chang, and Pulkkinen (2016), however, combine COR-2 and HI-1 observations to automatically detect CME leading edges in the imagery, and CACTusCAT, which automatically detects CMEs in HI, was produced as part of HELCATS (Pant et al, 2016). The merits and difficulties of the manual versus automaticdetection methods are tackled directly by Yashiro, Michalek, and Gopalswamy (2008), who compare the CDAW and CACTus data sets.…”
Section: Introductionmentioning
confidence: 99%
“…Barnard et al (2015) reported on a semi-automatic method (J-tracker) using STEREO HI data. Kirnosov, Chang, and Pulkkinen (2016) presented results in automatic tracking of CMEs using COR2 and HI-1 images. All these methods were applied to a reduced set of events.…”
Section: Introductionmentioning
confidence: 99%